Improvement of non-uniform node deployment mechanism for corona-based wireless sensor networks - Hamid Ekal, Hassan (2019)
The promising technology of Wireless Sensor Networks (WSNs), lots of applications have been developed for monitoring and tracking in military, commercial, and educational environments. Imbalance energy of sensors causes significant reduction in the lifetime of the network. In corona-based Wireless Sensor Networks (WSNs), nodes that are positioned in coronas near the sink drain their energy faster than others as they are burdened with relaying traffic come from distant coronas forming energy holes in the network. This situation shows significant effects on the network efficiency in terms of lifetime and energy consumption. The network may stop operation prematurely even though there is much energy left unused at the distant nodes. In this thesis, non-uniform node deployments and energy provisioning strategies are proposed to mitigate energy holes problem. These strategies concerns the optimal number of sensors required in each corona in order to balance the energy consumption and to meet the coverage and connectivity requirements in the network. In order to achieve this aim, the number of sensors should be optimized to create sub-balanced coronas in the sense of energy consumption. The energy provisioning technique is proposed for harmonizing the energy consumption among coronas by computing the extra needed energy in every corona. In the proposed mechanism, the energy required in each corona for balanced energy consumption is computed by determining the initial energy in each node with respect to its corona, and according to the corona load while satisfying the network coverage and connectivity requirements. The theoretical design and modeling of the proposed sensors placement strategy promise a considerable improvement in the lifetime of corona-based networks. The proposed technique could improve the network lifetime noticeably via fair balancing of energy consumption ratio among coronas about 9.4 times more than other work. This is confirmed by the evaluation results that have been showed that the proposed solution offers efficient energy distribution that can enhance the lifetime about 40% compared to previous research works.